Differences between sample form and its effect on sensitivity of composite propellants containing bicyclo-HMX as a new energetic additive - Sazeček, Filip; Vodochodský, Ondřej; Matyáš, Robert; Pachman, Jiří (Univerzita Pardubice, 2022)
This paper presents the results of friction and impact sensitivity of a modern energetic additive cis-1,3,4,6-tetranitro-octahydroimidazo-[4,5-d]imidazole (bicyclo-HMX, BCHMX) incorporated into a composite propellant. The effect of the concentration of energetic additive on friction and impact was studied. The results were compared with its structural analogue HMX and with the unmodified Control propellant. Plates and powdered propellant were used as samples in order to investigate the differences between the form of the sample and its response to mechanical stimuli. The FEST method was used for evaluation of the sensitivity.
Rozdíly mezi formou vzorku a jejím vlivem na citlivost heterogenních propelentů obsahující bicyklo-HMX jako nové energetické aditivum
Keywords: composite propellants; nitramine propellants; sensitivity; heterogenní propelenty; nitraminové propelenty; citlivostní charakteristiky